Spectral Curves of Operators with Elliptic Coefficients - Eilbeck, J.C.; Enolski, V.Z.; Previato, E. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
A computer-algebra aided method is carried out, for determining geometric objects associated to differential operators that satisfy the elliptic ansatz. This results in examples of Lamé curves with double reduction and in the explicit reduction of the theta function of a Halphen curve.